PENGARUH RELIGIUSITAS, KEPERCAYAAN MEREK, DAN KEPUASAN MEREK TERHADAP LOYALITAS KONSUMEN PRODUK HALAL DI SHOPEE - Muhamad Gibran Akbar Pangestu; Jaharuddin Jaharuddin (Taksasila Edukasi Insani, 2025)
This study aims to examine the influence of religiosity, brand trust, and brand satisfaction on consumer loyalty toward halal products on the Shopee platform. The background of this research lies in the increasing interest of Muslim consumers in halal products and the growing trend of online shopping (e-commerce). Consumer loyalty is one of the key indicators in maintaining business sustainability, especially in the digital halal industry.This research adopts a quantitative approach using a survey method through questionnaires distributed to 221 Shopee users who purchase halal products. The sampling technique used was purposive sampling. Data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The variables in this study include religiosity, brand trust, and brand satisfaction as independent variables, and consumer loyalty as the dependent variable.The results indicate that brand trust and brand satisfaction have a significant positive effect on consumer loyalty. However, religiosity does not significantly influence loyalty. These findings suggest that although religious values are important, consumer experience and perception toward brands play a more dominant role in shaping loyalty on digital platforms. This study contributes to the literature on halal marketing and provides practical insights for business actors and e-commerce platforms in developing consumer loyalty strategies for Muslim markets.Keywords: religiosity; brand trust; brand satisfaction; consumer loyalty; halal products; Shopee